Building capacity in reducing population dietary sodium intake in the Americas - Lorena Andrea Allemandi; Nadia Flexner; Leo Nederveen; Fabio da Silva Gomes (Pan American Health Organization, 2022)
Objective. To present some resources developed as part of the technical support of the Pan American Health Organization (PAHO) to Member States to reduce population dietary sodium intake, and to discuss the main challenges and opportunities to accelerate action toward sodium intake reduction in the Americas. Methods. Sources of information include a mapping of salt reduction policies conducted in 2019, reports from working group meetings, interviews conducted in 2020 and 2021 in seven countries, and technical documents developed around the Updated PAHO Regional Sodium Reduction Targets. Results. These tools show that, despite progress, challenges to succeed in this agenda persist. Priority given to sodium reduction is low in most countries, with insufficient resource allocation. There is a lack of intersectoral coordinated action, and a systemic approach to food systems is commonly missing. Surveillance mechanisms of sodium intake are insufficient, and industry interference in policy processes is commonly identified, undermining policy progress and success. There are also important regional opportunities to address these challenges. These include common ground for future collaborations by updating, strengthening, and complementing these existing tools, and technical and financial support for data generation. Conclusions. PAHO is committed to continue to support countries in the process of promoting, implementing, and monitoring cost-effective sodium reduction interventions. One key policy priority in this agenda is the adoption of the Updated PAHO Regional Sodium Reduction Targets with a mandatory approach, together with the comprehensive and complementary implementation of other strategies. Strong political will and commitment of countries will be critical to translate goals into concrete achievements in the Americas.